APPROACH AND PRINCIPLES RELATED TO THE FORMATION OF READING COMPREHENSION SKILLS - Berdiyeva Nilufar Ibodullayevna (American Journals, 2024)
This article explores the approach and principles related to the formation of reading comprehension skills. It delves into the theoretical underpinnings and practical implications of teaching reading comprehension, emphasizing the importance of fostering a comprehensive understanding of texts among learners. The article highlights various approaches to reading comprehension instruction, including schema theory, cognitive strategies, and metacognitive awareness. It discusses the role of background knowledge, vocabulary development, and textual analysis in enhancing reading comprehension skills. Furthermore, it addresses the principles of scaffolding and differentiated instruction, which aim to support learners of diverse backgrounds and abilities. Drawing from interdisciplinary perspectives in education, psychology, and linguistics, the article provides insights into effective pedagogical strategies and instructional methodologies for fostering reading comprehension skills. It underscores the significance of engaging students in active reading, critical thinking, and reflective practices to promote deeper comprehension and meaning-making. Overall, this article serves as a valuable resource for educators, curriculum developers, and researchers seeking to enhance reading instruction and literacy development across diverse educational contexts.
Keywords: 1. Reading comprehension 2. Approach 3. Principles 4. Literacy education 5. Schema theory 6. Cognitive strategies 7. Metacognition 8. Vocabulary development 9. Scaffolding 10. Differentiated instruction 11.Socio-cultural perspectives